Occupational self-efficacy scale: validity in teachers - Dominguez-Vergara, Julio (2024)
Occupational self-efficacy has gained attention because of its importance in understanding the effects of psychosocial factors at work, but because of its relevance, it is necessary to study it in the context of the COVID-19 pandemic. The Occupational Self-Efficacy Short Scale Form (OSS-SF) is a measure of individual variability in selfefficacy within the work context and has been used in some studies in Latin America. The aim of this study was to obtain evidence of the validity of the OSS-SF for 214 Peruvian teachers and to evaluate its internal structure and associations with other constructs. The sample, composed of 214 teachers (Mage = 44, SDage = 10), was selected using nonprobabilistic convenience sampling and evaluated via online forms. Nonparametric item response theory was used. Among the results, a unidimensional structure and high scalability at the item and scale levels were obtained (>0.70). The reliability was approximately 0.90. There was moderate convergence with job satisfaction (0.39) and slight convergence with the perception of the management of virtual tools (0.18). The OSS-SF is a scale with adequate evidence of validity and reliability for Peruvian teachers who work remotely. Therefore, it can be used as a diagnostic measure of intervention and training needs to benefit teachers and students.